Isolasi Antimikroba Baru dari Bakteri Tanah - Evi Damayanti; Firdaus Hamid; Rizalinda Sjahril (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Antimicrobial resistance has become a problem and a threat to health both in Indonesia and in the world. Resistance is the ability of bacteria to neutralize and weaken the action of antibiotics. The aim of this study was to isolate a novel antimicrobial from soil bacteria. The method used in this research is exploratory. The test bacteria used were Staphylococcus aureus and Pseudomonas aeruginosa. The results showed that there were two isolates that had zones of inhibition against the test bacteria staphylococcus aureus, namely isolates T2.2 and T2.18. The results of the first antimicrobial test for isolate T2.2 showed that the inhibition zone formed was 14.05 mm and isolates T2.18 the inhibition zone formed was 11.96 mm. The results of the second antimicrobial test were carried out by treating the unheated T2.2 isolate which showed an inhibition zone formed of 15.53 mm and the heated one 15.46 mm, while the unheated T2.18 isolate showed an average inhibition zone of 12.46 mm and heated 12.21 mm. The conclusion of this study is that the inhibition zone formed on isolates T2.2 and T2.18 is still relatively small and both isolates are spesies of Pseudomonas aeruginosa.